Daily Beneficial Effects of Work-to-Family Facilitation on Employees' Recovery and General Health: Is More Work Engagement Always Better? - Carmona-Cobo, Isabel; Blanco-Donoso, Luis Manuel; Garrosa, Eva (Frontiers in Psychology, 2021)
This study of 104 Chilean employees examines the process of WFF – recovery – general health on a daily basis. Drawing on the work–home resources (W-HR) model, we hypothesized that daily work-to-family facilitation and work engagement predict recovery experiences during off-job time in the evening (i.e., detachment from work and relaxation) and subsequent general health at night. Furthermore, we explored whether daily work engagement moderates the relationships between daily work-to-family facilitation and recovery experiences during off-job time in the evening and general health at night. In addition, we expected employees’ detachment from work to have a lagged effect on next-day general health at night. Participants completed a survey and a diary booklet over five consecutive working days (N = 520 occasions). Multilevel analyses show that, as expected, daily work-to-family facilitation predicted recovery experiences during off-job time in the evening (i.e., detachment from work and relaxation). However, contrary to our expectations, daily work engagement only predicted general health at night. Moreover, as expected, a moderation effect of daily work engagement shows that on days that employees experience low levels of daily work engagement, daily work-to-family facilitation is strongly related to detachment from work and relaxation during off-job time in the evening and to general health at night. Unexpectedly, on days on which employees experienced high levels of daily work engagement, daily work-to-family facilitation was weakly related to these outcomes. Finally, in accordance with our expectations, detachment from work had a lagged effect on next-day general health at night. These findings offer support for the W-HR model and have theoretical and practical implications for research and organizations.